Pembangunan Sistem Manajemen Dinas dan Laporan Harian Kru Jalan (Studi Kasus: PT. Akas Mila Sejahtera) - Kholish Ulil Abshor; Eriq Muhammad Adams Jonemaro; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
PT. Akas Mila Sejahtera (hereinafter referred to as Akas IV) is a bus service based company with economy and Patas classes. There are hundreds of buses and crews serving passengers every day. Even so, every duty recording and management of the Daily Report was still done manually. Dynamic duty changes in bus fleets and crews can lead to errors in recording by the Service Manager. The errors in recording can lead bus fail to depart because the crews were incomplete. In addition, because the sales of tickets were still carried out conventionally by the Conductor using official Akas IV ticket sheets, the Cashier was also recording the Daily Report manually. If there is a mismatch that lead a loss to the company, then it will be borne by the conductor. This has an impact on the income of the crews. Based on this statement, the solution chosen was to build a system that could manage the service and the crews Daily Report at Akas IV. The construction of this system uses a waterfall development model and an object-oriented approach. The system is built using web service technology because the system is built on a web and mobile platform. This system is tested using unit testing, integration testing, validation testing and compatibility testing strategies which showed valid results.